2016
DOI: 10.14569/ijacsa.2016.070602
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Software Testing: Thoughts, Strategies, Challenges, and Experimental Study

Abstract: Abstract-Mobile devices have become more pervasive in our daily lives, and are gradually replacing regular computers to perform traditional processes like Internet browsing, editing photos, playing videos and sound track, and reading different files. The importance of mobile devices in our life necessitates more concerns of the reliability and compatibility of mobile applications, and thus, testing these applications arises as an important phase in mobile devices adaption process. This paper addressed various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…One of the major challenges of Software Testing is Device Frag-mentation [32], [4], [19], [32], [45], [1], [14], [33]. Variations in the hardware or O.S.…”
Section: Device Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the major challenges of Software Testing is Device Frag-mentation [32], [4], [19], [32], [45], [1], [14], [33]. Variations in the hardware or O.S.…”
Section: Device Fragmentationmentioning
confidence: 99%
“…Variations in the hardware or O.S. components can cause mobile applications, while running on different devices, to behave differently where each application has its own unique business and data flow [1]. A study reported the existence of 1.800 hardware/O.S.…”
Section: Device Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer the questions above, the following requirements have been considered: a novel compatibility testing approach on global-scale (Akour et al , 2016); the individual developers and small teams cannot have all the different types of devices, so there is a need for outsourcing to obtain enough mobile devices models with different OS versions; manual compatibility testing method on a real mobile phone to address the automated testing issue; and an online public space that documenting good Android development knowledge and experiences to understand the overall architecture of Android. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the need for a generic solution to address compatibility issues mentioned above, we consider the following requirements in our proposed solution: (1) A new testing approach is required to support a global-scale mobile device compatibility testing [12];…”
Section: Introductionmentioning
confidence: 99%